Strategi Pengembangan Desa Wisata Edukasi di Desa Kajar Kecamatan Dawe Kabupaten Kudus - Ulfiatun Ni’mah; Abi Amar Zubair; Jenar Sara Pangesti; Nu’matul Uliyah; Noor Fatmawati (FKIP, Universitas Palangka Raya, 2024)
A strategy is needed to develop an educational tourism village in Kajar Village to increase visitors and community interest, preserve and maintain the potential of tourist attractions, and support empowerment strategies. The objectives of this research are: 1) identify educational tourism activities in Kajar Village. 2) Describe the internal and external factors that influence the development of an education-based tourism village in Kajar Village. 3) To find out strategies for developing an education-based tourism village in Kajar Village. This research uses a descriptive-qualitative approach. This research was carried out in Kajar Pine Park (Pijar), located in Kajar Village, Dawe District, Kudus Regency. Data was obtained by conducting interviews, direct observation, and documentation. Meanwhile, data analysis techniques involve data collection, reduction, presentation, and then concluding. The results of the research explain that the strategy for developing educational tourism in Kajar Village includes collaborating with various communities and with the local government to develop tourism through APBDes assistance, developing potential education-based tourist attractions, and increasing educational experts.